2016
DOI: 10.1371/journal.pone.0154373
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium Butyricum CGMCC0313.1 Modulates Lipid Profile, Insulin Resistance and Colon Homeostasis in Obese Mice

Abstract: Obesity is associated with a cluster of metabolic disorders and systemic low-grade inflammation involving multiple organs. Recent findings have suggested that intestine is a key organ altered in response to high fat diet (HFD) feeding. Probiotics mainly lactobacillus strains have earlier been implicated in alleviating metabolic disorders. Here we aimed to examine the effects of a naturally occurring butyrate-producing probiotic clostridium butyricum CGMCC0313.1 (CB0313.1) in limiting the development of HFD-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 33 publications
(45 reference statements)
5
75
0
3
Order By: Relevance
“…It has been demonstrated that CBM588 alleviated acute experimental colitis and high‐fat diet‐induced non‐alcoholic fatty liver disease . We have earlier shown that CB0313.1 improves type 1 diabetes and obesity . Herein, we extended beneficial effects of C. butyricum to experimental AP.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that CBM588 alleviated acute experimental colitis and high‐fat diet‐induced non‐alcoholic fatty liver disease . We have earlier shown that CB0313.1 improves type 1 diabetes and obesity . Herein, we extended beneficial effects of C. butyricum to experimental AP.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were then centrifuged at 14 000 g for 15 min at 4°C and supernatants were used for analysis. We used parameters of GC‐MS as previously described . Next‐generation sequencing was performed on an Illumina MiSeq system.…”
Section: Methodsmentioning
confidence: 99%
“…In adipose tissue, lower transcriptional levels of pro-inflammatory TNF-α, IL-6, IL-1β and monocyte chemotactic protein-1 in adipose tissue were observed in CB0313.1-treated mice. Collectively, the authors demonstrated that CB0313.1, targeting colon inflammation and permeability, ameliorated HFD-induced obesity, insulin resistance as well as adipose inflammation [7] . In the review: possible efficacy of Aloe Vera gel metabolites in long-term ingestion to insulin sensitivity, Yagi A. reported the beneficial effects of manno-oligosaccharide in Aloe Vera gel to gutbrain (hypothalamus) axis of hepatic glucose production and insulin sensitivity, and proposed an assumption based on a brain-liverintestine circuit to coordinate with insulin sensitivity of endogenous glucose production [1] .…”
Section: Effect Of Butyrate To Insulin Resis-tance and Energy Expendimentioning
confidence: 91%
“…Mice treated with CB0313.1 exhibited reduced lipid accumulation in liver and serum, lower circulating insulin levels and improved glucose tolerance and insulin sensitivity. CB0313.1, targeting colon inflammation and permeability, ameliorated HFD-induced obesity, insulin resistance as well as adipose inflammation [7] . Present review summarizes various mechanisms in which butyrate may influence brain health in a number of different neurological disorders.…”
Section: Possible Prophylaxes Of Aloe Vera Gel Ingestion To Butyrate mentioning
confidence: 99%
See 1 more Smart Citation